2004
DOI: 10.1074/jbc.m404962200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Leptin Binding Sites and Design of a Leptin Antagonist

Abstract: The leptin/leptin receptor system shows strong similarities to the long-chain cytokine interleukin-6 (IL-6) and granulocyte colony-stimulating factor cytokine/receptor systems. The IL-6 family cytokines interact with their receptors through three different binding sites I-III. The leptin structure was superposed on the crystal structures of several long-chain cytokines, and a series of leptin mutants was generated focusing on binding sites I-III. The effect of the mutations on leptin receptor (LR) signaling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
169
1
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(188 citation statements)
references
References 52 publications
6
169
1
12
Order By: Relevance
“…5) are structurally similar and face the same orientation, and they are most likely involved in interacting with CHR2. Mutations of those residues, such as D9S, T12Q, K15S, T16N, R20N, Q75S, N82S, D85S and L86A, L86S, L86N, and L86Q, significantly lowered the affinity of leptin for CHR2 and affected both binding and leptin receptor signaling (4,5). To date, no report regarding the putative role of Asp-23 has been published; nevertheless, our data (see Table 3) strongly indicate that replacement of Asp-23 by any non-negatively charged amino acid is sufficient to increase affinity for hLBD (CHR2) and subsequent biological activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5) are structurally similar and face the same orientation, and they are most likely involved in interacting with CHR2. Mutations of those residues, such as D9S, T12Q, K15S, T16N, R20N, Q75S, N82S, D85S and L86A, L86S, L86N, and L86Q, significantly lowered the affinity of leptin for CHR2 and affected both binding and leptin receptor signaling (4,5). To date, no report regarding the putative role of Asp-23 has been published; nevertheless, our data (see Table 3) strongly indicate that replacement of Asp-23 by any non-negatively charged amino acid is sufficient to increase affinity for hLBD (CHR2) and subsequent biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although several theoretical models of such a complex have been proposed (4 -6), lack of a valid crystallographic structure hampers reliable structural interpretation of any new leptin mutations. In the last decade, leptin has also been documented as a major regulator of the innate and adaptive immune response and a modulator of the onset and progression of autoimmunity in several animal models of disease (7), including rheumatoid arthritis, experimental autoimmune encephalomyelitis (4), and immune-mediated colitis (8). Work published from our and others' laboratories has also shown that leptin enhances thioacetamide-induced liver fibrosis (9) and liver inflammation in several mouse models (10).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…To test the generality of the antibody-CDR fusion approach, we next attempted to fuse human leptin, also a member of the four-helix-bundle hormone family, into the Herceptin CDR3 regions of the heavy and light chains. Previous studies have indicated that residues at the N terminus of helix D of hLeptin are essential for binding to and activating hLeptin receptor (38,39). These residues are on the opposite face of hLeptin relative to the free N and C termini.…”
Section: Resultsmentioning
confidence: 99%